Inflationary Expectations and the Demand for Money: The Greek Experience "A Comment and Some Different Results" – A Rejoinder - Dimitris Panayotopoulos (Kredit und Kapital, 1984)
"Ein Kommentar und einige abweichende Ergebnisse" zu "Inflationserwartungen und Geldnachfrage: die Erfahrungen Griechenlands" - Eine Erwiderung Beide Autoren, B-L und Himarios, haben die Nachfrage für die M,-Funktion nicht korrekt geschätzt. Die Nachfrage nach M, ist in Griechenland sehr instabil. Wenn man das Jahr 1973 als Schnittstelle nimmt, dann zeigt die Schätzung, daß sich die Parameter der Nachfragefunktion für M,seit 1973 signifikant verändert haben. – – Inflationary Expectations and the Demand for Money: The Greek Experience "A Comment and Some Different Results" - A Rejoinder Both writers, B-L and Himarios, have not estimated correctly the demand for M, function. The demand for M, in Greece is highly unstable. Taking as a cut-off point the year 1973, the estimation shows that the parameters of the demand for M, function have undergone significant shift since 1973.
Keywords: 330